The persistent religious gender gap in the Netherlands in times of secularization, 1966-2015 - Kregting, Joris (Interreligious studies, 2019)
"Over the last 50 years, the Netherlands has undergone a process of massive secularisation, in terms of the decline of institutionalised religion. This study tests a wide range of explanations for this process, built on modernisation theory, with high quality survey data. In addition, despite modernisation and the rise of gender equality in the area of social structural location, a religious gender gap persists in the Netherlands with women being more religious than men. With a comprehensive model of social and psychological differences between Dutch men and women, this study contributes to an explanation for this gap." --back cover